2014
DOI: 10.1111/jsap.12179
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease associated with red complex bacteria in dogs

Abstract: The results indicate that involvement of red complex bacteria in periodontal disease in dogs is similar to that observed in humans. Only the concurrent presence of T. forsythia and P. gingivalis were correlated to periodontal disease in dogs in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…As transmission of oral bacteria during normal contacts between dogs and humans or through dog bites is feasible, one might expect correlations between the oral microflora of dogs and humans, suggesting the possibility of zoonotic effects, which has been reported by other researchers [1540]; however, such effects should be further investigated on a large scale. Moreover, rapid testing based on the real-time PCR method facilitates the choice of an appropriate pharmacological treatment, which is of particular importance considering the differences in the occurrence of individual bacteria in the subgingival area and their different sensitivity to antibiotics.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As transmission of oral bacteria during normal contacts between dogs and humans or through dog bites is feasible, one might expect correlations between the oral microflora of dogs and humans, suggesting the possibility of zoonotic effects, which has been reported by other researchers [1540]; however, such effects should be further investigated on a large scale. Moreover, rapid testing based on the real-time PCR method facilitates the choice of an appropriate pharmacological treatment, which is of particular importance considering the differences in the occurrence of individual bacteria in the subgingival area and their different sensitivity to antibiotics.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, it has been confirmed that age plays a significant part in the progression of periodontitis in both species [1519]. Yamasaki et al [40] demonstrated that the total bacteria count in dogs is positively correlated with animal age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontal disease is one of the most common diseases of adult dogs, with up to 80% of animals affected [23]. All canine breeds are at risk of developing periodontal disease [26]. In general, the disease is more prevalent in small breeds compared to large breeds, and incidence increases with advancing age.…”
Section: Periodontal Diseasementioning
confidence: 99%
“…The "red complex" bacteria Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia, are frequently isolated together and are strongly associated with advanced periodontal lesions (56,(87)(88)(89), but according to recent studies periodontal diseases are caused by synergistic and dysbiotic microbial community rather than "select periopathogens" such as "red complex" (88). So the concept of "red complex" has been superseded by the "Keystone pathogen" hypothesis, at least in mice.…”
Section: Porphyromonas Gingivalismentioning
confidence: 99%